The Role of Administrative Personnel in Improving the Quality of Services in Schools - Agustin, Desika; Imron, Ali; Mustiningsih, Mustiningsih (Proceedings Series of Educational Studies, 2024)
According to the author, the aim of the article is to analyze the role of administrative staff in improving the quality of services in schools. Administrative staff play an important role in supporting the educational process, starting from the role of administrative staff, the quality of educational administrative services, the role of administrative staff in improving the quality of services in schools. By optimizing the role and quality of services, schools can create an environment that is more efficient and responsive to the needs of students, parents and the community. This research uses a qualitative approach by reading various library sources and qualitative analysis as a data collection method. The results show that more professional and skilled administrative staff contribute significantly to improving service quality, both through the level of administrative services and the role of school administrative staff.